Effectiveness of family-based weight management interventions for children with overweight and obesity: an umbrella review. (July 2019) - Chai, Li Kheng; Collins, Clare; May, Chris; Brain, Katherine; Wong See, Denise; Burrows, Tracy
ABSTRACT: Objectives: The objective of the review was to synthesize the effectiveness and strategies used in family-based behavioral childhood obesity interventions in improving child weight-related outcomes. Introduction: Family-based interventions are common practice in the treatment of childhood obesity. Research suggests that direct parental involvement can improve child weight-related outcomes. However, challenges remain in assessing the effects of family-based interventions on child weight and weight-related behavior due to the lack of quality programs and diversity of treatment strategies. Inclusion criteria: The review included systematic reviews and/or meta-analyses of family-based behavioral interventions in children aged ⩽18 who were classified as overweight and/or obese, and which reported child weight related outcomes, such as body mass index (BMI), body fat percentage and waist circumferences. Methods: Seven databases were searched from 1990 to May 2016 to identify English language publications. Reference lists of included reviews and relevant registers were also searched for additional reviews. All included systematic reviews were critically appraised by two reviewers independently. Data extracted included characteristics of included systematic reviews and weight-related outcomes reported. Data synthesis involved categorizing the interventions into seven categories and presented findings in narrative and tabular format. Quality of evidence was assessed using the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) approach. Results: The umbrella review included 14 systematic reviews (low to moderate methodological quality), published between 2004 and 2015, including 47 independent trials ranging from one month to seven years follow-up conducted in more than 16 countries. The majority of reviews (93%) reported weight outcomes of children aged six to 13 years. All reviews except one indicated that family-based interventions were successful in improving child weight and/or weight-related behavior. Five reviews highlighted that parent-only interventions had similar (n = 4) or greater (n = 1) effectiveness compared to parent-child interventions. Effective interventions employed parent-targeted strategies, including nutrition and physical activity education sessions, positive parenting skills, role modelling and child behavior management to encourage positive healthy eating/exercise behaviors in children and/or whole family. Conclusions: Family-based interventions targeting parents, alone or with their child, are effective for child weight management. Due to the lack of high quality evidence, especially in emerging parent-only interventions, further research is warranted. Health practitioners can work with parents as agents of change and focus on fostering positive parenting skills, such as monitoring, reinforcement, role modelling, and providing a nurturing environment, in order to support health behaviors in their children. Future research needs to explore whether parent-only interventions are more cost-effective compared to parent-child interventions, and to include larger populations, longer intervention duration and follow-up.